A corporative justice. Knowledges, practices and judicial strategies into the Tribunal del Consulado in Buenos Aires (1794-1821) - Rodríguez, Benjamín Matías (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2013)
The present work aims at analyzing the knowledge and practices, as well as the judicial strategies that different traders put into play within the consular jurisdiction. These came largely from the business itself. That is why I consider them as an extension of their economic function as merchants. In this research, I will analyze the profiles of two important traders from the Plaza de Buenos Aires, who occupied, at different times, positions of importance in the government of the Consulate. Furthermore, I will show who the opponents are in the trials that are mentioned. Finally, I will point out the conflicts of each case. who occupied, at different times, positions of importance within the Consulate of Buenos Aires.